(untitled) (Castilla. Estudios de Literatura, 2013)
In spite of his aesthetic quality and his trangression capacity, Miguel Labordeta´s poetry (Zaragoza, 1921-1969) not enough attention has been paid in our literary history. The whole of his work has been excluded from the critical considerations which other contemporary authors included in the postwar period did have. The innovate sense of his writing and his complex and symbolic universe have probably kept the books of this Aragonese writer out of critical appreciation which states the singularity of his lyric inside a poetic scene characterized by a submission to the realism messages. The current essay sees to clarify some aspects which value the poetical writing of Miguel Labordeta.